The Efficacy of Chlorantraniliprole as a Seed Treatment for Mythimna separata (Walker) (Lepidoptera: Noctuidae) - Hongbo Li; Changgeng Dai; Yang Hu (Journal of Chemistry)
The oriental armyworm (OAW), Mythimna separata (Walker) (Lepidoptera: Noctuidae), is an important pest in China and causes serious economic losses in corn. The anthranilic diamide, chlorantraniliprole (CHL), has been widely used as a seed treatment to control corn pests; however, no information is available on the efficacy of this insecticide as a seed treatment for OAW. In this study, the efficacy of seed treatment with CHL alone and CHL combined with the neonicotinoid insecticide clothianidin (CHL + CLO) was evaluated for controlling OAW larvae in the laboratory and field conditions. Pot experiments demonstrated that seed treatment with CHL and CHL + CLO (both 240 g a.i. 100 kg−1 seeds) resulted in >79% mortality of OAW larvae and a damage rate <20% in corn at 14 days after seed emergence (DAE). Similar to results obtained in pots, the residual toxicity of CHL and CHL + CLO to OAW larvae in the field declined with DAE and larval development. The control efficacy of field plots treated with CHL and CHL + CLO was >70% within 14 DAE, which was significantly higher than CLO alone. These results suggest that CHL and CHL + CLO as seed treatments could effectively reduce OAW larval infestation in corn. This study validates the effectiveness of corn seed treatment for OAW as an alternative to conventional foliar applications.